Empowering Pesantren Students with Financial Technology Literacy at Dayah Darul Hikmah, Aceh Besar - Aqil, Atallah; Halim, Hendra; Mulana, Farid; Hamat, Zahri; Rezeki, Sri; Nasution, Lisa Elianti; Riyaldi, Muhammad Haris; Nizam, Ahmad; Fatahillah, Habib; Zahrani, Nazila (Jurnal Pengabdian Bakti Akademisi, 2025)
Financial technology (fintech) has rapidly transformed the financial sector, yet many Islamic boarding schools (pesantren) still lack adequate financial literacy, limiting students' access to digital financial services. This community service program aims to enhance fintech literacy among pesantren students by introducing Shariah-compliant financial technologies and their applications in daily financial management. The method used is service learning, combining theoretical education and hands-on practice through interactive workshops and fintech application simulations. The results indicate a significant improvement in students understanding of digital financial services, including the use of Islamic e-wallets, peer-to-peer lending, and crowdfunding platforms. However, challenges such as limited digital infrastructure and misconceptions about fintech remain. This initiative highlights the importance of continuous fintech education in pesantren to prepare students for the digital economy while ensuring compliance with Islamic financial principles. Strengthening digital access and regulatory support will be crucial for sustaining fintech literacy in Islamic educational institutions.